2016
DOI: 10.21873/anticanres.11239
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of PIWI-interacting RNA, piR-823, Are Deregulated in Tumor Tissue, Blood Serum and Urine of Patients with Renal Cell Carcinoma

Abstract: piR-823 is down-regulated in tumor tissue, but positively correlated with worse outcome, indicating its complex role in RCC pathogenesis. In blood serum, piR-823 is up-regulated, but with unsatisfactory analytical performance. Preliminary data indicate the promising diagnostic utility of urinary piR-823 in patients with RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 15 publications
0
69
0
1
Order By: Relevance
“…In 2015, Yang and colleagues (9) firstly described the presence of piR-57125 (DQ596014) in serum and plasma and proved that similarly to miRNAs, this piRNA remains extremely stable regardless of repetitive freeze-thawing or long-term incubation at room temperature. Since that time, several other articles described the presence of piRNAs in circulation and their deregulation in blood samples of cancer patients (8,20,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, Yang and colleagues (9) firstly described the presence of piR-57125 (DQ596014) in serum and plasma and proved that similarly to miRNAs, this piRNA remains extremely stable regardless of repetitive freeze-thawing or long-term incubation at room temperature. Since that time, several other articles described the presence of piRNAs in circulation and their deregulation in blood samples of cancer patients (8,20,35).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the authors further revealed that this piRNA plays a tumorpromoting role by upregulating phosphorylation and transcriptional activity of HSF1, the common transcription factor of heat shock proteins (19). Interestingly, piR-823 was also observed to be deregulated not only in tissue, but also in blood serum of patients with renal cell carcinoma (8) and gastric cancer (20). Currently, next-generation sequencing (NGS) is widely used to identify known as well as novel piRNAs with deregulated expression in cancer.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, xenograft nude mice model confirmed its tumor suppressive role in a dose-dependent manner, indicating that piR-823 play a crucial role in gastric cancer. Recently, Iliev et al demonstrated that piR-823 is down-regulated in tumor tissue, blood serum and urine of renal cell carcinoma (RCC) [86]. Law et al [87] identified a novel piR-Hep1 which is up-regulated in hepatocellular carcinoma (HCC) compared to adjacent non-malignant liver tissues through deep sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Snížené hladiny této piRNA byly zaznamenány u nádorů žaludku [59] či u pa cientů s renálním karcinomem [60], přičemž umělé navýšení hladiny piR-823 in vitro v buněčné linii odvozené od nádoru žaludku vedlo k významné inhibici růstu nádorových buněk. Nádorově supresorový efekt této piRNA byl následně potvrzen in vivo s využitím myšího modelu [61]. K opačným výsledkům dospěla studie zabývající se expresí piR-823 u mnohočetného myelomu.…”
Section: Piwi Proteiny a Kancerogenezeunclassified